2019
DOI: 10.4081/gc.2019.7961
|View full text |Cite
|
Sign up to set email alerts
|

The role of healthy nutrition and diet in the prevention of non-communicable diseases among the aged

Abstract: Non-communicable diseases (NCDs) kill approximately 41 million individuals every year, proportional to 71% of all deaths universally. This paper discuses the role of healthy nutrition and diet in the prevention of non-communicable diseases among the aged. It is a theoretical research in which Non-communicable diseases and the aged was discussed, and researched backed nutritional recommendations for the prevention of common non-communicable diseases, and other geriatric illnesses was extensively discussed under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…To this day, in many other parts of the world, MAPs are widely used as medication in various pathologies, even though a vast number of the world's flora (estimated over 500,000 species) remains uncharted in terms of pharmaceutical potential [27]. Natural products and especially MAPs have a wide range of vitamins, minerals, antioxidants, fiber, and fatty acids that attribute to several beneficial outcomes in non-communicable diseases (NCDs) prevention [28][29][30][31]. The dietary habits of subpopulations in Greece have been the item of previous research [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…To this day, in many other parts of the world, MAPs are widely used as medication in various pathologies, even though a vast number of the world's flora (estimated over 500,000 species) remains uncharted in terms of pharmaceutical potential [27]. Natural products and especially MAPs have a wide range of vitamins, minerals, antioxidants, fiber, and fatty acids that attribute to several beneficial outcomes in non-communicable diseases (NCDs) prevention [28][29][30][31]. The dietary habits of subpopulations in Greece have been the item of previous research [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Based on major health problems of older adults, health behaviors in this research focused on health-promoting behaviors for reducing NCD risk factors; tobacco use, alcohol consumption, dietary intake, and physical activity. 39 , 42 - 46 The IHPP-SP affected to protective factors including happiness, ADLs, family support, and healthy behaviors, although it did not differ regarding depression and alcohol consumption. Unlike some developed countries, this research defined older individuals starting at 60 years according to “The Act on Older Persons B.E.…”
Section: Discussionmentioning
confidence: 94%
“…The regular consumption of a healthy diet is one of the most important measures to have overall good health, as well as prevent the risk of having cancer in the future. 20) Findings from a systematic and metaanalytical study revealed that regular adherence to a Mediterranean food regimen reduced the risk of developing esophageal, colorectal, liver, lung, bladder, and stomach cancers in the future, as well as significantly reduced the risk of death and serious health outcomes in people who survived cancers. 21) This is possible through the modification and reduction of chemical enzymes and other growth hormones that increase the risk and development of cancer cells in the body.…”
Section: Adequate Consumption Of Healthy Dietsmentioning
confidence: 99%